2019
DOI: 10.3389/fphar.2019.01407
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Trans-4-Methoxy-β-Nitrostyrene in Spontaneously Hypertensive Rats: Comparison With Its Parent Drug β-Nitrostyrene

Abstract: We previously reported that trans-4-methoxy-β-nitrostyrene (T4MN) evoked higher vasorelaxant effects in small resistance arteries from spontaneously hypertensive rats (SHRs) in comparison with its parent drug, the β-nitrostyrene 1-nitro-2-phenylethene (NPe). To further our knowledge of the influence of insertion of an electron-releasing group such as methoxy in the aromatic ring of NPe, we investigated the cardiovascular responses to intravenous (i.v.) injection of T4MN in SHRs and compared with those of NPe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…A similar profile was recently reported in isolated small resistance arteries from SHRs, in which T4MN was 22 times more potent as a relaxing agent than NPe 25 . Furthermore, both T4MN and NPe elicited vago‐vagal bradycardia and hypotension, and T4MN was about 30 times more potent at recruiting chemosensitive pulmonary vagal afferent fibres than NPe 16 . Thus, it seems that introduction of a methoxy group into the aromatic moiety stabilizes NPe, thereby enhancing both its potency and its interaction with sGC.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A similar profile was recently reported in isolated small resistance arteries from SHRs, in which T4MN was 22 times more potent as a relaxing agent than NPe 25 . Furthermore, both T4MN and NPe elicited vago‐vagal bradycardia and hypotension, and T4MN was about 30 times more potent at recruiting chemosensitive pulmonary vagal afferent fibres than NPe 16 . Thus, it seems that introduction of a methoxy group into the aromatic moiety stabilizes NPe, thereby enhancing both its potency and its interaction with sGC.…”
Section: Discussionsupporting
confidence: 83%
“…Previous in vitro experiments using aortic rings from normotensive rats showed that the methoxy derivative, trans ‐ 4 ‐ methoxy ‐ β ‐ nitrostyrene (T4MN; Figure 1B), exerts vasorelaxant activity by stimulating the sGC/cGMP pathway independently of endothelial NO 15 . Interestingly, the vasorelaxant potency of T4MN in resistance arteries from SHRs was 22‐fold greater than that of its parent drug, NPe 16 . To better understand the influence of insertion of the electron‐releasing methoxy group in the aromatic ring of NPe, we investigated vasorelaxant effects of T4MN in isolated pulmonary artery from normotensive rats, and compared them with those of its parent drug, NPe.…”
Section: Introductionmentioning
confidence: 96%
“…Finally, it is suitable to assess the cardiovascular effects of T4CN in conscious rats. Previously, we showed that intravenous administration of 1‐nitro‐2‐phenylethane [47,48], NPe [49], T4MN [49], and T4MeN [50] elicited hypotensive and bradycardiac responses from vago‐vagal origin in rats.…”
Section: Discussionmentioning
confidence: 99%